Chromatic alteration in Arenaeus cribrarius (Lamarck) (Crustacea, Portunidae): an indicator of sexual maturity - Pinheiro, Marcelo Antonio Amaro [UNESP]; Taddei, Fabiano Gazzi [UNESP] (Sociedade Brasileira de Zoologia, 2000)
Some individuals of the species Arenaeus cribrarius (Lamarck, 1818) bear a characteristic pink abdomen, which is notably different from the usual white coloration. The incidence of this chromatic alteration was determined for a single population and its relation with other individual variables were examined. The individuals were monthly collected from May, 1991 to April, 1993, in Ubatuba, São Paulo, with the aid of a shrimp fishery boat provided with double-rig trawling nets. All specimens were sexed, measured (CW = carapace width), distributed in 10-mm size classes and classified according to growth phase (juvenile and adult), molting condition and development stage of gonads. The occurrence of pink-colored morphs was also recorded. From a total of 2,096 collected individuals, only 60 females (nine of those ovigerous) presented a pink-colored abdomen, which represents 2.9% of the whole sample and 5.2% of the females. Almost all of them were intermolt individuals (96.6%) and 63.3% showed mature gonads. According to published data, size at the onset of functional maturity in A. cribrarius females is around 60 mm CW, from which the incidence of pink morphs and ovigerous crabs were recorded. The obtained results suggest that such a chromatic alteration is associated to sexual maturity in these females. This characteristic may enhance the attraction potential for mating, shortly after the puberty molt.
Keywords: Brachyura; Portunidae; reproduction; coloration